Analysis of Passenger Handling, Baggage Volume, and Aircraft Rotation on Operational Cost Efficiency Mediated by on-time Performance at CITILINK Airlines - R Iskandar Ali; Zaenal Abidin; Reni Dian Octaviani (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to analyze the effect of passenger handling, baggage volume and aircraft rotation on operational cost effectiveness mediated by on-time performance at Citilink airlines. The problem in this study is that the influence between the independent variables (passenger handling, baggage volume, aircraft rotation) and the dependent variable (operational cost effectiveness) mediated by on-time performance is quite complex. The research design used is quantitative with data analysis using SEM PLS with 100 respondents consisting of operational officers, passenger handling, baggage handling and administration. where the significant level is 0.05 to state whether the null hypothesis or alternative hypothesis is accepted or rejected. The results showed that there is a significant influence between Passenger Handling and operational cost effectiveness with a P value of 0.023. There is a significant positive relationship between baggage volume and operational cost effectiveness with a P value of 0.005. The effect of aircraft rotation and operational cost effectiveness with a P value of 0.003 which means there is a significant influence. On-time performance has a very significant influence on operational cost effectiveness with a P value of 0.000. Passenger handling has a significant effect on on-time performance with a P value of 0.000. There is no significant influence between baggage volume and operational cost effectiveness through on-time performance with a P value of 0.156. The effect of aircraft rotation shows a significant effect on operational cost effectiveness through on-time performance with a P value of 0.000.